SELECTIVE CO-ACTIVATION OF NICOTINIC ACETLYCHOLINE RECEPTOR SUBTYPES RESTORES ALZHEIMER’S RELATED HIPPOCAMPAL DYSFUNCTION AND PATHOLOGY - Lee, Rahmi, author; Kim, Seonil, advisor; Tamkun, Michael, committee member; Tsunoda, Susan, committee member; Rojas, Donald, committee member (Colorado State University. Libraries, 2026)
Alzheimer’s disease (AD) is the most common form of dementia. It is a serious disease that not only affects the patient but also their caregivers because it is irreversible with many deteriorating symptoms with limited treatments that are very expensive. Most importantly, these treatments are not very effective. AD has two main pathological characteristics, amyloid plaques, whose main components are misfolded beta amyloid peptides (Aβ), and neurofibrillary tau tangles, where hyperphosphorylated tau proteins misfold and aggregate together to make helical filaments. Unfortunately, the cause of the disease is still unknown, and there is no cure. Previous preclinical and clinical trials for the treatment of AD have not been very successful due to a few reasons. For example, most patients join the study after their diagnosis has been made (the progression of the disease is too far for treatments to make an impact on the disease). Progress in the field is further constrained by the lack of reliable biomarkers for early detection of AD. Previous literature has shown that Aβ induces hyperexcitation in neurons, which can happen in multiple layers. At the neuronal level, Aβ can be seen to induce neuronal hyperexcitability. At the circuit level, an imbalance between the excitation and inhibition in excitatory cells and inhibitory interneurons induces hyperexcitation, which leads to impaired information processing. This can cause network dysfunction, resulting in cognitive decline. Unfortunately, the underlying mechanisms are unknown. Our previous findings, using cultured mouse hippocampal neurons show Aβ selectively interacts with α7- and α4β2-nicotinic acetylcholine receptors (nAChRs), but not α3β4-nAChRs, and decreases activity in inhibitory interneurons, leading to hyperexcitation in excitatory neurons. Moreover, we have shown that co-activation of α7- and α4β2-nAChRs is required to reverse the Aβ-induced adverse effects in hippocampal excitatory neurons. Here, we discover that α7- and α4β2-nAChRs predominantly control the nicotinic cholinergic signaling and neuronal activity in hippocampal parvalbumin-positive (PV+) and somatostatin-positive (SST+) inhibitory interneurons, respectively. We further reveal that selective co-activation of α7- and α4β2-nAChRs is necessary to reverse hippocampal network dysfunction, amyloid pathology, and fear memory loss in the amyloid pathology mouse model by enhancing hippocampal inhibition.